Perception of Students and Faculty about Mounted Display of Dry Human Bones as Visual Educational Tool - Jayaben Charania; Mangesh Lone; Nisha Randhir; Rohini Shete; Kishor Khushale (Dr. Chinmay Pandya, 2023)
This study aimed to assess the usefulness of mounted display boards of dry human bones as a self-directed learning tool for 1st year Bachelor of Medicine, Bachelor of Surgery (MBBS) students studying osteology. A prospective observational questionnaire-based study was conducted in a medical college attached to a tertiary care hospital in western Maharashtra. Feedback was obtained from 159 out of 200 participating students and was subjected for analysis. The results showed that the majority of students found the mounted display boards to be interesting (89%), beneficial for presentation skills (83%), improving thinking ability (82%), easing drawing tasks (62%), facilitating self-directed learning (79%), reducing mistakes during assessments (84%), enhancing subject understanding (91%), and promoting departmental involvement. The findings suggest that the development of department-specific display boards can enhance students' drawing skills, improve subject comprehension, thinking ability, and reduce errors made by students (75% students). Furthermore, the inclusion of charts with muscle attachments on the display boards was recommended by 94% students for additional utility. Overall, these findings highlight the significance of incorporating mounted display boards into anatomy departments as a valuable educational resource.